Approximate Controllability of Second-Order Distributed Systems - Henriquez-Miranda, H (John Wiley and Sons Ltd, 2014)
In this paper, we study the approximate controllability of control systems with state and control in Banach spaces and described by a second-order semilinear abstract differential equation. We compare the approximate controllability of the system with the approximate controllability of an associated discrete system. Copyright © 2013 John Wiley & Sons, Ltd.